Language, culture and society - Mananay, Janet A.; Sumalinog, Gino G. (Lorimar Publishing Inc., 2021)
This is aligned to the current trends in education such as constructivist, integrative, interactive, collaborative, inquiry-based, brain-based, research-based, and reflective teaching-learning.